BOARDING-BASED SCHOOL PROGRAM; INNOVATIVE APPROACHES TO NOURISHING RELIGIOUS CHARACTER VALUES - Abqoriy, Muhammad; Suhardi, Andi; Sahlan, Moh (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The aim of this research was to describe the concept of the Islamic boarding school-based school program in instilling students' religious character values and to determine the implementation and evaluation of the Islamic boarding school-based school program in instilling students' religious character values. The research method used a qualitative approach with a case study type of research. Data collection techniques include observation, interviews and documentation. Data analysis used the Miles and Huberman model, namely data collection, data reduction, data presentation and drawing conclusions. The results of this research were first, the Islamic boarding school-based school program is a program that integrates the curriculum in public schools with that in Islamic boarding schools which was launched by SMPN 2 Pasirian in collaboration with the Nurul Hayat Pasirian Islamic Boarding School. This program was a form of supporting and strengthening religious character education in students, especially regarding learning Islamic religious education (PAI). Second, this program was implemented from Monday to Thursday and during non-school hours, namely 13.00-15.00. The learning materials taught were reading and writing the Qur'an, memorizing short surahs, basic fiqh, and learning basic Arabic. Apart from that, the religious habituation model was also applied during school hours such as Duha prayers, reading Asmaul Husna or short surahs from the Al-Qur’an, giving alms in the form of money every Friday to be distributed to school students in need, and so on. Third, evaluate this program through three domains, namely the cognitive, affective and psychomotor domains.